FUNDAMENTAL BASES FOR CREATING SUSTAINABLE LAWN PHYTOCENOSIS - F. A. Gastasheva; E. N. Didanova (Новые технологии, 2020)
The article presents the results of studies of the allelopathic properties of perennial gasforming plants adapted to the abiotic and adaphic conditions of the foothill zone of the KBR. The decrease in the stability of agrocenosis, especially in mixed crops, is associated with the allelopathic activity of the plants that make up the cenosis. The objects of the research are phytocenoses designed in two ways: continuous and strip. The phytocenosis consists of pasture ryegrass (Lolium perenne L.), meadow bluegrass (Poa praténsis L.), metropolitan bent (Agróstis stolonífera L.), red fescue (Festuca rubra L.), sheep fescue (Festuca ovina L.). The results of studies of the allelopathic properties of ragweed and the possibility of inhibiting its growth and development with some cereal components of lawn phytocenosis were obtained. Allelopathic activity of perennial cereal plants in clean crops was lower than in mixed phytocenosis. Pure crops of sheep fescue (Festuca ovina L.) and red fescue (Festuca rubra L.) had low allelopathic activity of 28 UEK) and 35 UEK respectively. Metropolitan bent (Agróstis stolonífera L.) and pasture ryegrass (Lolium perenne L.) had the highest allelopathic activity, 94 UEK and 78 UEK respectively.In the third year of the functioning of the lawn phytocenosis, the competitive power of ragweed decreased 1.75 times in the strip structure of the phytocenosis and 3.99 times in the continuous structure of the phytocenosis. The results of the study can be used to combat segetal vegetation, in particular, wormwood in the residential zone by creating stable lawn phytocenoses.